Social anxiety in first-episode psychosis: the role of childhood trauma and adult attachment - Michail, Maria; Birchwood, Max (Elsevier, 2014)
Background: Social anxiety is among the most prevalent affective disturbances among people with psychosis. The developmental pathways associated with its emergence in psychosis, however, remain unclear. The aim of this study is to identify the developmental risk factors associated with social anxiety disorder in first-episode psychosis and to investigate whether social anxiety in psychosis and nonpsychosis is associated with similar or different adult attachment styles. Method: This is a cross-sectional study. A sample of individuals with social anxiety disorder (with or without psychosis) was compared with a sample with psychosis only and healthy controls on childhood trauma, dysfunctional parenting and adult attachment. Results: Childhood trauma and dysfunctional parenting (po0.05) were significantly elevated in people with social anxiety (with or without psychosis) compared to those with psychosis only and healthy controls. There were no differences in childhood trauma and dysfunctional parenting between socially anxious people with and without psychosis. Higher levels of insecure adult attachment (x2₁=38.5, p<0.01) were reported in the social anxiety group (with or without psychosis) compared to the psychosis only and healthy controls. Childhood adversities were not associated with insecure adult attachment in people with social anxiety (with or without psychosis). Limitations: Due to the cross-sectional nature of the study we cannot infer causal relationships between early risk factors, including childhood trauma and dysfunctional parenting, and social anxiety. Also, the use of self-report measures of attachment could be subject to biases. Conclusion: Shared developmental risk factors are implicated in the emergence of affective disorders in psychosis and non-psychosis. Social anxiety in psychosis is associated with insecurity in adult attachments which does not arise a result of adverse developmental pathways. Understanding the bio-psycho-social risk factors for affective dysregulation in psychosis could inform psychological interventions about the role of developmental anomaly and trauma in the emergence of affective dysregulation in psychosis.